Effect of Different Dietary Lipid Levels on Spawning Performance and Egg Quality of Pangasianodon hypophthalmus (Sauvage, 1878) - Muhammad Anamul, Kabir; Mohammad Badrul, Munir; Sharifah Lia Farliana, Wan Alias; Adriana Leja, Jenang; Lee, Seong Wei; Roshada, Hashim (Asian Fisheries Society, 2019)
Dietary lipid manipulation of broodstock diet offers a strategy for improving spawning performance and egg quality of broodstock fish. Although many studies were conducted on basic nutrient requirements for fingerlings and juveniles of Pangasianodon hypophthalmus (Sauvage, 1878); the artificial feed for P. hypophthalmus broodstock is still lacking. This study analysed the effect of different levels of lipid in the diet on spawning performance and egg quality of female P. hypophthalmus broodstock. Three test diets were formulated containing 1:1 ratio of palm oil and fish oil blends at the level of 60, 90 and 120 g.kg-1 with a constant 300 g.kg-1 protein and fed to triplicate groups of female broodstock for 150 days at the rate of 20 g.kg-1 body weight twice daily. The ovary weight, gonadosomatic index, fecundity, egg weight and diameter and egg fertilisation rate were significantly (P < 0.05) increased for fish fed with 90 and 120 g.kg-1 lipid diet compared to 60 g.kg-1 lipid diet. However, there was no significant difference between fish fed with 90 and 120 g.kg-1 lipid diet; thus an increase in dietary lipid above 90 g.kg-1 would not make any significant contribution. The increased performance of female broodstock fed with higher dietary lipid and fish oil at the ratio of 1:1 for crude palm oil and fish oil up to 90 g.kg-1 contributed in the enhancement of the reproductive performance and egg quality of P. hypophthalmus.